FACILITATING LISTENING COMPONENT IN EPP MASTER PROGRAMMES IN ECONOMIC UNIVERSITIES - Gavrilova, Elena; Trostina, Kira (European Scientific Journal, ESJ, 2015)
Foreign language Master programmes in Russian economic universities crown the hierarchy of linguistic training the students get during their academic studies. The English for Professional Purposes course being elective, the EPP teachers have to offer their potential students really outstanding input to encourage them to choose it in preference to other elective programmes. Master students attending EPP lessons generally have very high expectations from them as they directly link their proficiency in professional English with their future employability. Thus the EPP course delivered has to contain varied linguistic input to train students in all language skills, and listening skills in particular. The conducted research justifies that one of the most problematic aspects of teaching EPP is finding sufficient samples of listening in specific areas. Analyzing the applicability of available sources such as textbooks and Internet-sites, the authors suggest how appropriate audio material selection and consequent processing can completely reshape the course design and significantly boost listening practices at MA level in economic universities.